Bones, Bombs, and Break Points: The Geography of Economic Activity - Davis, Donald R; Weinstein, David E (American Economic Review, 2002)
We consider the distribution of economic activity within a country in light of three leading theories—increasing returns, random growth, and locational fundamentals. To do so, we examine the distribution of regional population in Japan from the Stone Age to the modern era. We also consider the Allied bombing of Japanese cities in WWII as a shock to relative city sizes. Our results support a hybrid theory in which locational fundamentals establish the spatial pattern of relative regional densities, but increasing returns help to determine the degree of spatial differentiation. Long-run city size is robust even to large temporary shocks.